Evaluation of the Performance of Newborn Screening for Tyrosinemia Type 1 in The Netherlands: Suggestions for Improvements Using Additional Biomarkers in Addition to Succinylacetone - Marelle J. Bouva; Allysa M. Kuypers; Evelien A. Kemper; Rose E. Maase; Annet M. Bosch; Francjan J. van Spronsen; Annemieke C. Heijboer; M. Rebecca Heiner-Fokkema; Sandra G. Heil; Anita Boelen (International Journal of Neonatal Screening, 2025)
Currently, Dutch newborns are screened for tyrosinemia type 1 (TT1) using succinylacetone (SA) as the biomarker. Although the sensitivity of the test is high, a high number of false positives is observed. Here, the aim is to evaluate the current Dutch newborn-screening protocol and to assess alternatives, specifically the use of biomarkers that are already being measured, to increase the positive predictive value (PPV). TT1 screening was performed with the Revvity NeoBase assay between 2008 and 2017, and since 2018, the Revvity NeoBase 2 assay has been used. Data from 2018 to 2021 were used for evaluation. To simulate alternative screening protocols, these data were enriched with results of referrals from other periods and a false negative (FN) from 2010. In 2018–2021, 693,821 newborns were screened, resulting in 23 referrals, of whom two were TT1 patients. For this period, to date, no FN have been reported, resulting in a provisional sensitivity of 100%, a specificity of 99.997%, and a PPV and negative predictive value of 9% and 100%, respectively. To improve the PPV, we combined SA, tyrosine (tyr), tyr × SA and tyr/phenylalanine and achieved a PPV of 72% for this dataset without introducing FN in the original dataset. This illustrates that future screening for TT1 may benefit from the addition of these biomarkers.